Building the House of Care for people with long-term conditions: the foundation of the House of Care framework - Coulter, A; Kramer, G; Warren, T; Salisbury, C (Royal College of General Practitioners, 2016)
The House of Care (HoC) is a framework for a coordinated service model that enables patients with long-term conditions (LTCs) and clinicians to work together to determine and shape the support needed to enable them to live well with their condition. Based on the internationally well-known Chronic Care Model2 but specifically adapted to fit UK primary care, it uses the metaphor of a house to describe the components that need to be in place to make coordinated personalised care planning a reality. Previous articles in this series have described various components of the House. This article focuses on its foundation.